GOD’S POLITICAL POWER IN WESTERN AND EASTERN CHRISTIANITY IN COMPARATIVE PERSPECTIVE - Diamantides, Marinos ca. 21. Jh. (Divus Thomas, 2012)
The distinction “constitutive-constituted” legislative power in normative and political understandings of the collective constitution historically derives from the distinction potentia absoluta/potentia ordinata. In this connection the paper: (a) affirms the continuing relevance of these theo-political distinctions in the, now globalised, West which it originally traces in developments between the eleventh and thirteen centuries in occidental Europe; (b) on the basis of these distinctions’ contingency and original cultural particularity, the paper exposes the pseudo-universal and even retroactive manner in which political theory and constitutional jurisprudence “project” specifically occidental concerns with absolute and acceptable theopolitical power to others with particular emphasis on ancient Israel and Byzantium considered, respectively, theocratic and caesaropapist; (c) because the comparative study of political theologies reveals the particularity and contingency of the major problems and solutions of modern political philosophy and theory, the paper ends with reference to what Merleau-Ponty called “perceptual faith” – a philosophical notion that allows us to go beyond both the “certainties” offered by transcendent philosophy and the “pragmatism” offered by empiricism, namely the two philosophies that predominate in liberal constitutional regimes. La distinzione tra potere legislativo “costituente” e potere legislativo “costituito”, secondo un’interpretazione normativa e politica della nozione di costituzione collettiva, è qui rivista alla luce della distinzione tra potentia absoluta e ordinata. In linea con questa considerazione di fondo, il saggio: (a) afferma la rilevanza attuale di una simile distinzione teologico-politica, il cui naturale sviluppo pur si situa nell’Europa occidentale dei secoli dall’undicesimo al quattordicesimo; (b) in relazione al problema contingente oggetto di questa distinzione e sulla base della sua originale peculiarità culturale, si espone il modo, pseudo-universale e persino retroattivo, attraverso cui la teoria politica e la giurisprudenza costituzionale “declinano” questioni tipicamente occidentali, inerenti in particolare l’indagine sul potere assoluto e che hanno dato luogo ad un sistema dottrinario in sé coerente dal punto di vita teologico-politico, in altre direzioni, con una speciale attenzione all’antico Israele e a Bisanzio, definiti rispettivamente teocratico e cesaropapista; (c) dal momento che lo studio comparato delle teologie politiche prese in esame rivela la particolarità e contingenza dei principali problemi e soluzioni della moderna filosofia e teoria politiche, il saggio termina riferendosi a quello che Merleau-Ponty chiamava “perceptual faith” – un concetto filosofico che ci consente, in definitiva, di andare ad un tempo oltre le “certezze” offerte dalla filosofia del “trascendente” e oltre il “pragmatismo” proposto dall’empirismo, ovvero le due filosofie dominanti nei regimi a costituzione liberale.